1243 Sentinel Lymph Node Biopsy for Melanoma during the COVID-19 Pandemic. (12th October 2021) - Stubley, T; El-Khayat, B
Abstract: Aim: Sentinel lymph node biopsy (SLNB) is an established aspect of the staging process for primary melanoma, with the results dictating future treatment methods. Due to the COVID-19 pandemic no SLNBs were offered to patients with newly diagnosed melanoma at a hospital site in the West Midlands. The aim of this study was to identify the number of patients who missed out on this investigation in order to ascertain how many patients with a potential positive SLNB were missed. Method: A patient list was provided from the dermatology and plastic surgery database, ensuring that all newly diagnosed melanoma patients throughout the period March-May 2020 were included. A retrospective study design was utilised, with all data collected from the computer system at a single hospital site. Results: 64 patients were provided via the patient list, of which 44 were appropriate for SLNB using the NICE criteria. After detailed reading of the patient notes, 80% (35/44) of patients were provided with a reason why they did not receive a SLNB, however the remaining 20% (9/44) did not have this clearly recorded. Conclusions: A large cohort of patients did not receive a SLNB during the COVID-19 pandemic. Utilising the clinical literature, it can be predicted that around 9 of these patients would have had a SLNB that identified metastasis. These patients have potentially missed out on adjuvant treatment, and the cohort will therefore require follow up to be adapted to reflect this.